THE CAUSATIVE VERBS ANALYSIS IN INDINA JONES AND THE LOST TREASURE OF SHEBA NOVEL - Jimmi (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2024)
The purpose of this research is to analyze and to identify a causative verb which is found on the novel of Indiana Jones and The lost treasure of Sheba. The writer uses descriptive qualitative method as guide to accomplish this research. The writer also does some steps, they are: collecting data, reading the novel to look for the causative been used, analyzing the datas and making conclussion. The datas are collected from references books, websites, and some articles. In this research, the writer would like to to analyze and explain how the use of causative verb in this novel such as let, help, get, make, and help. Furthermore, the result is the causative verb has been found as much 30 times whereas divided into 6 times for word of get, 2 times for the word of have, once for the word of make, 2 times for the word of help, and 19 times for the word of let.